2021
DOI: 10.1097/tp.0000000000003627
|View full text |Cite|
|
Sign up to set email alerts
|

Treating Type 1 Diabetes by Pancreas Transplant Alone: A Cohort Study on Actual Long-term (10 Years) Efficacy and Safety

Abstract: Patient and pancreas survival after PTA. Patient (upper black line) and pancreas (lower dashed line) survival over 10 y follow-up in 66 subjects with type 1 diabetic and with PTA. Pancreas survival includes grafts with optimal function and graft with good function (n: 2, passed from optimal to good function at 1 and 8 y after transplantation). Functional definition was according to Ref. 29. PTA, pancreas transplant alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
(158 reference statements)
2
10
0
Order By: Relevance
“…Pancreas transplantation in unstable patients with type I diabetes restores normoglycemia and avoids disease-associated complications. 109 Although considered a quality-of-life operation, data suggest the lifesaving nature of pancreas transplantation 110 ; however, IRI-associated pancreatitis and thrombosis can negatively impact transplantation outcomes. NMP may ameliorate pancreas IRI and allow β-cell function assessment before transplantation.…”
Section: Promising Nmp Systems In Other Organsmentioning
confidence: 99%
“…Pancreas transplantation in unstable patients with type I diabetes restores normoglycemia and avoids disease-associated complications. 109 Although considered a quality-of-life operation, data suggest the lifesaving nature of pancreas transplantation 110 ; however, IRI-associated pancreatitis and thrombosis can negatively impact transplantation outcomes. NMP may ameliorate pancreas IRI and allow β-cell function assessment before transplantation.…”
Section: Promising Nmp Systems In Other Organsmentioning
confidence: 99%
“…After pancreas transplantation was performed, the interest of conducting numerous studies concerning porcine islets transplantation emerged, which revealed it to be a promising treatment to cure diabetic patients 61 . Regarding the autologous regulatory T cell, no negative effects were seen related to the T regulatory cells infusion, regardless of cell dose.…”
Section: Therapeutic Valuementioning
confidence: 99%
“…Additionally, candidates with potentially life-threatening metabolic complications from hyperlabile diabetes, such as hypoglycemia unawareness, recurrent episodes of ketoacidosis, or progressive nonrenal complications may benefit from pancreas transplant alone (PTA) in the absence of a kidney transplant [10,11,12 ▪ ,13 ▪ ]. For this group of patients, it is essential that renal function be preserved in order to proceed with PTx.…”
Section: Options For Pancreas and Kidney Transplantation In Patients ...mentioning
confidence: 99%
“…Consequently, PTA became a Medicare-approved procedure in April 2006. A successful PTx is currently the only definitive long-term treatment that restores normal glucose homeostasis and may prevent, stabilize, or even reverse progressive diabetic complications [10,11,12 ▪ ,20–27]. Guidelines for referral for PTx are listed in Fig.…”
Section: Options For Pancreas and Kidney Transplantation In Patients ...mentioning
confidence: 99%